E-204 Novel blood analogue for in-vitro neurovascular modeling. (4th August 2020) - Sodawalla, H; Merritt, W; Becker, T
Abstract : Introduction: In-vitro models for simulating surgical procedures is a cost-effective way of creating fail-safe surgical protocols. Insights gained from these models can also aid in testing new medical devices and reduce the use of animal models. Traditional glass- and silicone-based in-vitro models use distilled water with surfactant additives for lubricity. However, a new material, carboxymethyl cellulose (CMC) dissolved in distilled water, can mimic the mechanical and rheological properties of blood. We have shown that CMC fluid out-performs distilled water, glycerol mixtures, and bovine blood, in terms of physiological accuracy. Methods: We tested the density and dynamic viscosity of the following blood analogs: CMC, distilled water, glycerol mixture (22 wt%), bovine blood ( Bos taurus ). For each material, samples were tested with a 20 mm cylindrical parallel plate head geometry (0.25 ml) attached to a hybrid rheometer (DHR-2, TA Instruments), set at 37°C (human physiological temperature). Three samples of each blood analog were tested and repeated 5 times. A shear rate sweep from 15 to 105 1/s was tested to cover a wide range of physiological blood flow rates. Results: We compared the density and dynamic viscosity of different materials in table 1 . Different CMC fluid concentrations and the resulting viscosity ranges are compared to blood with increasing shear rate (figure 1 ). CMC matches the initial viscosity and undergoes shear-thinning like human blood. Distilled water has a lower viscosity than blood that does not change with shear rate. It was found that CMC (1% wt) is closest to the material properties of human blood flow at the Circle of Willis (CW). Conclusion: CMC fluid is a promising tool in investigating blood flow characteristics in a bench-top model. It can mimic accurate physiologically relevant mechanical properties of blood and has the potential of being used as a go-to tool for medical device testing applications. This fluid will be able to minimize friction between synthetic vessels and endovascular devices and enhance the accuracy of simulated surgery models. Disclosures: H. Sodawalla: None. W. Merritt: None. T. Becker: 1; C; NIH STTR Phase I (#1R41NS097069-01A1).